When Does Inter-Jurisdictional Competition Engender a "Race to the Bottom"? A Meta-Regression Analysis - Joan Costa-i-Font; Filipe De-Albuquerque; Hristos Doucouliagos (Center for Economic Studies and ifo Institute (CESifo), 2015)
A growing literature documents the existence of strategic political reactions to public expenditure in one jurisdiction on either neighboring or reference jurisdictions. The latter might give raise to downward expenditure spiral, or race to the bottom . However, in ascertaining the empirical triggers of such a process evidence is suggestive of markedly heterogeneous findings. Most of such heterogeneity can be traced back to study design and institutional differences. This paper contributes to the literature by applying meta-regression analysis to quantify the size and the direction of strategic inter-jurisdictional expenditure interactions controlling for study and institutional characteristics. We find several robust results beyond confirming that jurisdictions do engage in strategic expenditure interactions; namely that (i) interactions are weakening over time; (ii) strategic interactions are stronger among municipalities than among intermediate levels of government; and (iii) strategic interactions appear to emerge from tax competition rather than yardstick competition, with capital controls and fiscal decentralization shaping the magnitude of fiscal interactions. Hence, we conclude political decentralization structures that draw upon the political agency (yardstick competition) does not necessarily engender a race to the bottom'.
Keywords: H10; H50; 330; inter-jurisdictional competition; yardstick competition; meta-regression; expenditure competition